2020
DOI: 10.1002/chem.202003852
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Twofold Electrochemical C−H Amination of Activated Arenes: Application to Medicinally Relevant Precursor Synthesis

Abstract: The efficientp roduction of many medicinally or synthetically importants tarting materials suffers from wasteful or toxic precursors for the synthesis. In particular,the aromatic non-protected primary amine functionr epresents a versatile synthetic precursor,b ut its synthesis typicallyr equires toxic oxidizing agentsa nd transition metal catalysts. The twofold electrochemical aminationo fa ctivated benzene derivatives via Zincke intermediates provides an alternative sustainable strategy for the formation of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…As one of the most important C-heteroatom connections, considerable efforts have been made to construct C-N bonds, including electrochemical protocols [31][32][33] . In recent years, the electrochemical dehydrogenative intermolecular construction of C-N bonds has witnessed tremendous progress, for example, in reactions of aromatic C-H amination [34][35][36][37][38][39][40][41][42][43] , benzylic C-H amination [44][45][46] , alkyne amination 47 , alkene azidation 48 , alkane amination 49 , aromatic C-X/N-H cross coupling [50][51][52][53] , alkene aziridination 49,[54][55][56][57][58][59] , and other innovations 60 . Despite these achievements, electricity has not fulfilled the task of sewing NH 3 and alkene to aromatic Nheterocycles.…”
mentioning
confidence: 99%
“…As one of the most important C-heteroatom connections, considerable efforts have been made to construct C-N bonds, including electrochemical protocols [31][32][33] . In recent years, the electrochemical dehydrogenative intermolecular construction of C-N bonds has witnessed tremendous progress, for example, in reactions of aromatic C-H amination [34][35][36][37][38][39][40][41][42][43] , benzylic C-H amination [44][45][46] , alkyne amination 47 , alkene azidation 48 , alkane amination 49 , aromatic C-X/N-H cross coupling [50][51][52][53] , alkene aziridination 49,[54][55][56][57][58][59] , and other innovations 60 . Despite these achievements, electricity has not fulfilled the task of sewing NH 3 and alkene to aromatic Nheterocycles.…”
mentioning
confidence: 99%
“…[9] It has also been demonstrated that installation of a nitrogen-containing heterocyclic system to the triterpenoid scaffold can greatly improve their biological activity. [10] 1,2,3-Triazoles as a common example of azoles are mostly introduced using the copper(I)-catalyzed alkyne-azide cycloaddition reaction on O-or N-propargyl function installed at different positions (C(3), C (28), C( 19)) of the betulin scaffold. [11] On the other hand, isoxazole moiety also belongs to the accepted linkers [12] and amide isosteres [13] in medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] Recently, electrosynthesis was employed to generate anti-tumor agents. [28] Against the background of the increasing expansion of the renewable energy sector, [29] electricity is thus up to becoming the green reagent of the 21 st century and economically attractive. [30] Here we report electro-organic synthesis of exceptionally stable betulin-derived nitrile oxide and its further transformation into novel C(17)-linked lupane-type triterpenoid-isoxazole hybrids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative to photocatalytic oxidation strategies, electrochemical methods have been developed to enable the amination of C­(sp)–H, C­(sp 2 )–H, and benzylic C­(sp 3 )–H bonds. , In fact, synthetic electrochemistry offers several advantages compared to traditional synthetic methods: (i) electrons can be considered as traceless reagents, (ii) no external oxidants or homogeneous metal catalysts are needed, and (iii) the selectivity can be tuned via the applied potential. Moreover, many technical issues previously related to electrochemical systems are now considered overcome, spurring renewed interest in electrochemical synthetic chemistry . Concerning electrochemical azolation reactions (Scheme C), several notable strategies have been developed in the past years by the groups of Yoshida, Devillers, Li, Lei, , Wu, and Liu .…”
mentioning
confidence: 99%